Model of Kalitidu Traditional Market's Off-Street Parking Requirements - Agustin, Imma Widyawati; Heptafiansyah, Rico Aagus; Widartiningsih, Nurizka Aprilia; Hasyim, Abdul Wahid; Munenge, Sizyoongo; Simamba, Habeenzu (Civil and Environmental Science Journal (CIVENSE), 2024)
The Market is one land use activity that can have an impact on congestion. Situated in Kalitidu District, Kalitidu Market serves as a Regional Service Center (PPK) for the Bojonegoro Regency. As Kalitidu Market is a market in the PKK region of Bojonegoro Regency, its operations frequently result in traffic jams. The study's goal was to predict Kalitidu Market's parking demands using multiple linear regression analysis, off-street parking user characteristic analysis, and the calculation of off-street parking capacity needs. For two-wheeled automobiles in the Kalitidu market, the following model is used to determine parking space requirements: Ya = 0,071 (X5) – (1,257 -0,005(X1) + 0,012(X2) + 0,012(X3) -57,044(X4) + 0,002(X6). The number of cars entering the area, the number leaving it, the number of vehicles entering the area initially, the amount of time the vehicles are parked, and the number of guests bringing vehicles are all factors that affect the requirement for parking for two-wheeled vehicles. 34 vehicles per hour are therefore required to have parking spaces for two-wheeled cars.